The Impact of Contextual Ambidexterity on the Internationalisation of Born Global Firms - Yein, Min Thu (My University, 2025)
Born global firms (BGFs) have accelerated their international expansion even earlier than was anticipated. That unprecedented acceleration has occasioned a reconsideration of traditional internationalisation theories. Why are certain companies able to accelerate their international expansion so rapidly? What are the dynamic organisational capabilities that are successfully under highly volatile global economic conditions? Organisational ambidexterity is defined as the ability to balance exploration and exploitation, and it has been recognised increasingly as a critical determinant of firm performance. The specific mechanisms and micro-foundations through which contextual ambidexterity is achieved within BGFs that are resource constraints as well as the gaps while the speed of international expansion still needs to be examined. The goal of this article is to investigate the components and origins of contextual ambidexterity, which is operationalised as Dual Network Capability (DNC), and to examine its relationship with the internationalisation speed characteristic of BGFs. The research is conceptually grounded in the Dynamic Capabilities View (DCV) and utilise micro-foundations perspective to clarify the individual level characteristics underpinning these organisational capabilities. A qualitative research design was implemented in the form of multiple case studies. This method was chosen as it is well aligned to investigating complex, environment specific phenomena and could help to open “the black box” of organisational ambidexterity. Data were collected through in-depth, semi-structured interviews of Top Management Team (TMT) members from two BGFs from emerging economies. The data collected has been analysed using thematic analysis following Braun and Clarke’s method. The results of the study indicate that TMT human capital and managerial cognition serve as critical micro-foundations and influencing factors, directly affecting the strategic capacity for ambidextrous activities. The case companies combine structural elements with individual-level flexibility to manage contradictory demands which reflects a hybrid ambidexterity model. The theoretical proposition that the beneficial effect of contextual ambidexterity on international success is indirect, manifested in intermediate outcomes such as increased international opportunity after recognition and closing deals, rather than directly related to overall firm performance was confirmed. Crucially, the effectiveness of ambidexterity development also depends primarily to external conditions and institutional environments, and cultural norms determine first and foremost the dynamic balance needed between exploration and exploitation. This research provides a rare empirical basis for capability and reinforces the need for hybrid models for emerging market firms operating in turbulent environments.
Keywords: internationalisation; small and medium-sized enterprises; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business